Ground reaction force across the transition during sprint acceleration. (25th November 2019) - Nagahara, Ryu; Kanehisa, Hiroaki; Fukunaga, Tetsuo
Abstract : Abrupt changes in kinematics during sprint acceleration called transitions have previously been observed. This study aimed to examine whether ground reaction force (GRF) variables during sprint acceleration also show specific features of the transitions. Twenty‐one male sprinters performed 60‐m sprints, during which GRF data were recorded. Step‐to‐step spatiotemporal and GRF variables were approximated using an exponential function and three straight lines. Moreover, statistical parametric mapping (SPM) was used to test changes in GRF curves across the transitions. For running speed, the exponential approximation resulted in smaller root‐mean‐square (RMS) of residuals. For the other variables, however, RMS of residuals was smaller when the three lines approximation was adopted. Breakpoints around the 5th and 15th steps were detected using effective vertical impulse during the braking phase with the three lines approximation. Across the breakpoints, SPM showed significant differences in the antero‐posterior GRF curves at the next step after the first breakpoint and at the second breakpoint. Moreover, the second braking phase of the antero‐posterior GRF appeared at the next step after the first breakpoint, and the corresponding first propulsive phase disappeared at the second breakpoint. Consequently, changes in GRF variables during sprint acceleration are likely accompanied by specific alterations. The breakpoints around the 5th and 15th steps found in an effective vertical impulse during the braking phase can be a criterion indicating transitions in GRF variables during sprint acceleration. The transitions are characterized by an appearance and disappearance of the second braking and first propulsive phases, respectively, of the antero‐posterior GRF.